The Outcomes of Corporate Governance to Financial Performance: Empirical Evidence from a Developing Country - Aseh, Khairi; Pathmanathan, P. Ravindran (Archives of Business Research, 2020)
Corporate governance has received increasing attention in the corporate world in these days. It is seen as a moral obligation and includes supporting the consistency of the law and showing ethical guidance. In this study, we attempted to examine the impact of corporate governance on corporate financial performance in Kuala Lumpur using a sample of 215 companies.Corporate governance variables have been shown to have a significant impact on corporate financial performance and market value measurement in general. The makeup of the board had a major positive impact on the ROA assessment variables, respectively. In addition, the CEO duality was positively correlated with all dependent variables, and the number of board committees was found to be negatively correlated with all measured variables, only significantly correlated with ROA. KEYWORDS: Corporate governance, financial performance, Kuala Lumpur